2004
DOI: 10.1002/mrd.20100
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of bovine sperm protease BSp120 by light and electron microscopy during capacitation and the acrosome reaction: Its role in in vitro fertilization

Abstract: Mammalian fertilization involves various steps in which the participation of specific enzymes has been demonstrated by numerous studies. Acrosin is one of the most widely acrosomal protease in mammalian spermatozoa studied, including bovine; however, other proteases have also been described. A new trypsin-like serine protease named bovine serine protease of 120 kDa (BSp120) and its pre-cursor BSp66 (66 kDa) were identified in bovine spermatozoa. Cytological and ultrastructural immunolocalization studies on BSp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…AR induction depicted a different exposure of BSp66 in hamster live spermatozoa, showing that BSp66 was located not only over the external membranes but also within the acrosomal content, as described for acrosin (Honda et al 2002). These results are consistent with our previous findings in bovine spermatozoa (Cesari et al 2004b).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…AR induction depicted a different exposure of BSp66 in hamster live spermatozoa, showing that BSp66 was located not only over the external membranes but also within the acrosomal content, as described for acrosin (Honda et al 2002). These results are consistent with our previous findings in bovine spermatozoa (Cesari et al 2004b).…”
Section: Discussionsupporting
confidence: 91%
“…The capacitation period involves surface changes in several species (Visconti et al 1999), some of them associated with the unmasking of surface receptors such as the progesterone receptor (Sirivaidyapong et al 2001, Pietrobon et al 2003. In agreement with these findings, our previous results with live bovine spermatozoa showed that capacitation induction promoted the exposure of BSp66 onto the sperm surface, and a redistribution during the AR (Cesari et al 2004b). As BSp66 codifying genes were not yet identified, we ignored this protein if it was expressed in the spermatogonial cell or if it was superficially acquired during the journey across the male duct (Boue et al 1992).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations